2016
DOI: 10.1186/s13568-016-0240-x
|View full text |Cite
|
Sign up to set email alerts
|

GST activity and membrane lipid saturation prevents mesotrione-induced cellular damage in Pantoea ananatis

Abstract: Callisto®, containing the active ingredient mesotrione (2-[4-methylsulfonyl-2-nitrobenzoyl]1,3-cyclohenanedione), is a selective herbicide that controls weeds in corn crops and is a potential environmental contaminant. The objective of this work was to evaluate enzymatic and structural changes in Pantoea ananatis, a strain isolated from water, in response to exposure to this herbicide. Despite degradation of mesotrione, probably due a glutathione-S-transferase (GST) pathway in Pantoea ananatis, this herbicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…The number of viable cells in the control and herbicide treatment groups is shown in Fig 2 . Generally, the strains behaved differently during treatment with mesotrione or Callisto [ 4 , 5 , 6 ]. For strain CCT 7729, treatment with mesotrione resulted in a large decrease in viable cell numbers by 14 h. In contrast, treatment with Callisto resulted in increased growth by 14 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of viable cells in the control and herbicide treatment groups is shown in Fig 2 . Generally, the strains behaved differently during treatment with mesotrione or Callisto [ 4 , 5 , 6 ]. For strain CCT 7729, treatment with mesotrione resulted in a large decrease in viable cell numbers by 14 h. In contrast, treatment with Callisto resulted in increased growth by 14 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications to membrane lipids was determined using the method of Prione et al [ 6 ]. Bacterial cultures were centrifuged at 8,000 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A toxicity study of sulcotrione (90) showed up-regulation of the genes inducing ROS and antioxidant enzymes in the fava bean cells (Vicia faba), followed by increased lipid peroxidation. Some pathogens, in turn, such as E. coli DH5-α (91) and Pantoea ananatis (92), showed resistance to oxidative stress caused by mesotrione, while human liver cancer Hepg2 cells were only mildly affected by tembotrione (93).…”
Section: -Hydroxyphenylpyruvate Dioxygenase Inhibitorsmentioning
confidence: 99%
“…Notably, contaminated environments expose microbiomes to stressful and selective conditions, and once microorganisms exhibit structural and metabolic adaptations, they can overcome these conditions and survive. These adaptive strategies are linked at the cellular level and to specific populations, allowing different responses to compounds such as pesticides [2,3] and enabling their use in biotechnological processes such as agrochemical degradation [46]…”
Section: Introductionmentioning
confidence: 99%